(3QSGdI aj GdCUhds - (3GdbheTgj, eMeO egOjs
(3ChdgG (B:s
(3HSe Gddg(B...(3aj NHQ GdhGMO GdYGQj Yf GdbQGFf GdeajOI ddbWY aj GdUOhQ Ch GdeVehf Ch geG eYG hJMbjbg jMJGL Edi HjGf ebOeI(B...s
(3BNQgG (B:s
...(3eY Cfg de jbe Odjd Ydi GYJHGQg TQYG (B...(3hYdjg aGdCUd QGLM Yd GdXf bO Je GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3hbagG eDdagG Ydi WdGH GdfLa GdCTQa HJGQjN (B19 (3ThGd (B1281(3g`s
Keywords: (3CUhd Gdabgs